Complement activation drives the phagocytosis of necrotic cell debris and resolution of liver injury - Vandendriessche, Sofie; Mattos, Matheus Silvério; Bialek, Emilia Laura; Schuermans, Sara; Proost, Paul; Marques, Pedro Elias (Frontiers in Immunology, 2024)
Cells die by necrosis due to excessive chemical or thermal stress, leading to plasma membrane rupture, release of intracellular components and severe inflammation. The clearance of necrotic cell debris is crucial for tissue recovery and injury resolution, however, the underlying mechanisms are still poorly understood, especially in vivo. This study examined the role of complement proteins in promoting clearance of necrotic cell debris by leukocytes and their influence on liver regeneration. We found that independently of the type of necrotic liver injury, either acetaminophen (APAP) overdose or thermal injury, complement proteins C1q and (i)C3b were deposited specifically on necrotic lesions via the activation of the classical pathway. Importantly, C3 deficiency led to a significant accumulation of necrotic debris and impairment of liver recovery in mice, which was attributed to decreased phagocytosis of debris by recruited neutrophils in vivo. Monocytes and macrophages also took part in debris clearance, although the necessity of C3 and CD11b was dependent on the specific type of necrotic liver injury. Using human neutrophils, we showed that absence of C3 or C1q caused a reduction in the volume of necrotic debris that is phagocytosed, indicating that complement promotes effective debris uptake in mice and humans. Moreover, internalization of opsonized debris induced the expression of pro-resolving genes in a C3-dependent manner, supporting the notion that debris clearance favors the resolution of inflammation. In summary, complement activation at injury sites is a pivotal event for necrotic debris clearance by phagocytes and determinant for efficient recovery from tissue injury.